Exploring the therapeutic potential of precision medicine in rare genetic obesity disorders: a scientific perspective - Collet, Tinh-Hai; Schwitzgebel, Valerie (Frontiers in Nutrition, 2024)
The prevalence of obesity is increasing worldwide, affecting both children and adults. This obesity epidemic is mostly driven by an increase in energy intake (abundance of highly palatable energydense food and drinks) and to a lesser degree a decrease in energy expenditure (sedentary lifestyle).A small proportion of individuals with obesity are affected by genetic forms of obesity, which often relate to mutations in the leptin-melanocortin pathway or are part of syndromes such as the Bardet-Biedl syndrome. These rare forms of obesity have provided valuable insights into the genetic architecture of obesity. Recent advances in understanding the molecular mechanisms that control appetite, hunger, and satiety have led to the development of drugs that can override genetic defects, enabling precision treatment. Leptin deficiency is uniquely treated with recombinant human metreleptin, while those with LEPR, PCSK1, or POMC deficiency can now be treated with the MC4R agonist setmelanotide. This review highlights the most frequent monogenic and syndromic forms of obesity, and the future outlook of precision treatment for these conditions.